PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA REALISTIK PADA POKOK BAHASAN LINGKARAN KELAS VIII SMP - Santi, Dewi; Sugiarti, Titik; Kristiana, Arika Indah (Department of Mathematics Education , University of Jember, 2015)
Abstract. The research aims to know the process and result of development of mathematics learning materials based on realistic mathemathics education for circle topic. Learning materialsdevelopment model refers to 4D Thiagarajanmodels which has 4 steps namely define, design, develop, and disseminate. The subject of research is students of VIII-A class SMPN 2 Wuluhan in even semester academic year 2013-2014.The data of research are obtained by validation sheet, observation sheet of teacher and students activities, questionnaire, and evaluation test. Theproducts of this research are lesson plan, student handbook, worksheet, and evaluation test.The result shows that the learning materialsqualifies validity, practical, and effective criteria.Based on validation process and tryout, the result shows that the coefficient of validity reachs 3 point, the percentages of teacher’s activities, students’ activities, and students’ responses are above 80%, it can be concluded that the learning instruments had fullfiledthe validity, practice, and effective criteria. Key Words: 4DThiagarajanmodels, realictic mathemathics education, circle.